Beyond Resource Constraints: How Participatory Management Practices Foster Teacher Pedagogical Competence - Dewi Nurmayasari; Okke Rosmaladewi (Papanda Publisher, 2026)
Educational quality in integrated junior high schools operating under severe resource constraints remains critically dependent on effective principal management, yet systematic understanding of how principals successfully foster teacher pedagogical competence development in such contexts remains limited. This study examined principal management practices in improving teacher pedagogical competence at integrated junior high schools through planning, organizing, actuating, and controlling functions. A qualitative case study approach was employed at two purposively selected integrated junior high schools in Purwakarta Regency, Indonesia. Data were collected through in-depth interviews with 18 participants (principals, vice principals, teachers, and students), participant observation, and document analysis. Data analysis followed Miles, Huberman, and Saldaña's interactive model, with triangulation ensuring credibility. Findings revealed substantial differences between schools despite similar resource limitations. SMPN Satu Atap Cileunca's participatory planning, distributed organizational structures, systematic implementation, and documented evaluation fostered greater teacher agency and professional development compared to SMPN Satu Atap Panyindangan's centralized, informal approach. Key differentiating factors included collaborative planning processes, peer learning structures, consistent supervisory practices, and systematic documentation. Management effectiveness in resource-constrained contexts depends fundamentally on participatory, adaptive approaches rather than resource abundance. Strategic management practices emphasizing collaboration and systematic improvement can successfully cultivate teacher pedagogical competence even under severe constraints, challenging deficit-oriented perspectives and offering actionable guidance for principals, supervisors, and policymakers in developing contexts.